Induced abortion during youth: social inequalities in the outcome of the first pregnancy - Menezes Greice M. S.; Aquino Estela M. L.; Silva Diorlene Oliveira da (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2006)
This study aimed to identify the factors associated with induced abortion in the first pregnancy in young women and in the first time young men got their partners pregnant. The methodology was a household survey with face-to-face interviews in a probabilistic sample in three stages with 4,634 subjects, aged 18 to 24 years of age residing in the cities of Salvador, Rio de Janeiro, and Porto Alegre, Brazil. Logistic regression analysis was used with a hierarchical strategy for entering variables into the model. Abortion was the reported outcome of the first pregnancy for 16.7% of the women and 45.9% of the men (in relation to their partners). Key factors associated with abortion included higher schooling and the occasional nature of the relationship with the male or female partner in the respective pregnancy. Inclusion of males in the study provided new elements for understanding the abortion phenomenon, including in the gender issues in discussion of the theme. The authors recommend greater public investment to warrant access to information and means for young people to achieve their reproductive plans in a security and healthy way, respecting their sexual and reproductive rights.